SCREENING ACTIVITY OF LIPOLYTIC BACTERIA: BIOFOULING COMPLEX ON SURAMADU CONCRETE BRIDGE SUBSTRATE - Junaedi, Abdus Salam; Atho’illah, M; Tasya, Friska Rachmawati; Farid, Akhmad (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2025)
Biofouling is an aquatic biota that lives by attaching to a harmful substrate. Bacteria are one of the factors in the formation of biofouling communities on the substrate. Lipolytic bacteria are microorganisms capable of degrading lipid (fat) compounds. The purpose of this study aimed to determine the characteristics of lipolytic bacteria that were successfully isolated from a sample of the Suramadu concrete bridge substrate (Surabaya-Madura waters). There are 3 sampling stations doing 3 repetitions at each station. The isolation method used was a pour plate using selective Stone Mineral Salt Solution Extract Yeast Agar (SMSSEYA) + 2% bacto agar media . The results showed that the characterization of bacterial colonies in Surabaya-Madura waters obtained 5 types of bacterial colonies namely BL1, BL2, BL3, BL4, and BL5. The lipolytic indexes of bacteria BL2, BL3, and BL4 were respectively 0.51; 1.31; 0.78 mm and types of bacteria BL1 and BL5 with a value of 0 mm each. Bacteria types BL2, BL3, and BL4 are lipolytic bacterial isolates because they are capable of producing extracellular lipase enzymes characterized by the formation of clear zone areas surrounding the bacterial colonies.